Application of Interactive English E-Module with Flipbook Application for Early Childhood Education Students - Saputri, Tiyas; Djuwari, D; Authar, Nailul; Asmara, Berda; Putri Rahmadani, Nabila; Rokhman Saleh, Nanang; Ayu Chrestina, Devi (UKInstitute, 2022)
Education is one of the pillars of the progress of a nation. Education is still a serious concern in each region in order to increase. The quality of education at the Integrated Early Childhood Post (PPT) Kuncup Melati Surabaya is quite good but still needs to be improved. One of them is in technology-based English learning. Learning English at PPT Kuncup Melati Surabaya will be much more interesting if it is packaged with a blend of technology and presented to Early Childhood Education students in the form of visual learning. In addition, online learning is currently being promoted again along with the increasing number of Covid-19 victims during this pandemic. Mastery of technology-based English learning at PPT Kuncup Melati Surabaya is still minimal. This is evident from the learning that is still carried out face-to-face, even though it is carried out in alternating schedules. Even though there are clear rules from the government that suggest that learning is done online. As a solution, assistance is needed in technology-based online English learning with a variety of methods and is carried out in a sustainable manner so that learning can be done online but still interesting. By applying the flipbook application in learning English, it is hoped that it will stimulate Early Childhood Education students in learning technology-based English. Flipbook is a powerful software application designed to convert PDF files to page-turning digital publications. With the flipbook application, a digital bookshelf can be created from several E-Modules that have been produced so that teachers and students can choose which E-Module to read by simply pressing the click button to select it. This Community Service (PKM) activity plan is focused on implementing an interactive English E-Module with a flipbook application for Early Childhood Education students at PPT Kuncup Melati Surabaya. The target of this PKM activity is the students in the school. The expected output is to apply a flipbook application to students at the school and to create a digital literacy corner and e-learning regeneration which is expected to be able to increase the knowledge, skills, interests and motivation of Early Childhood Education students in learning English. With the digital literacy corner, it is hoped that it can increase student interest in literacy.